2022
DOI: 10.4314/kje.v3i1.17
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Influence of Digital Technology on Undergraduate Students’ Academics in University of Maiduguri, Borno State, Nigeria

Abstract: This study was conducted to determine the influence of digital technology on undergraduate students’ academics. It was guided by two objectives and one null hypothesis. Descriptive survey research design was adopted for the study. A sample of 378 undergraduate students was used for the study using a multistage sampling technique. Perceived Influence of Digital Technology on Undergraduate Students’ Academics Questionnaire (PIDTUSAQ) was used as an instrument for data collection. Cronbach Alpha analysis was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…However, the findings seem to be at variance with those of other studies (Akhlaq, Amjad, Mehmood, Hussan & Malik, 2010). The findings lent credence to those that indicated that the personal variables such as location of school plays a significant role in the perception of various sources of stress related to the teaching profession (Parray, Kumar, & Awasthi, 2016;Maduagwu, Nelson-Okarter, Ezekiel, 2019). On the other hand, Valkov and Peeva (2020) reported that there was no significant difference the stress levels experienced by teachers in urban and rural settings a finding which may have been as result of moderating factors such as age, sex, marital status, financial status, years of teaching, and physical activity that were included in the previous study.…”
Section: Discussionsupporting
confidence: 74%
“…However, the findings seem to be at variance with those of other studies (Akhlaq, Amjad, Mehmood, Hussan & Malik, 2010). The findings lent credence to those that indicated that the personal variables such as location of school plays a significant role in the perception of various sources of stress related to the teaching profession (Parray, Kumar, & Awasthi, 2016;Maduagwu, Nelson-Okarter, Ezekiel, 2019). On the other hand, Valkov and Peeva (2020) reported that there was no significant difference the stress levels experienced by teachers in urban and rural settings a finding which may have been as result of moderating factors such as age, sex, marital status, financial status, years of teaching, and physical activity that were included in the previous study.…”
Section: Discussionsupporting
confidence: 74%